PENGARUH MINAT NASABAH TERHADAP PRODUK DEPOSITO - Fahlevi, Muhammad Ryan; UmpuSinga, Hasrun Afandi; Nizaruddin, Nizaruddin; Anjasari, Dwi Puspa (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
This study has the aim of knowing the effect of interest in the Influence of Customer Interest on Deposit Products, this research was conducted at the Islamic People's Financing Bank Metro Madani Metro Head Office (BPRS Metro Madani KP Metro), BPRS Metro Madani KP Metro is one of the financial institutions based In sharia, there are several fund-raising products that use the profit-sharing principle that is offered, one of which is a deposit product. The research was conducted by regression analysis. The population in this study was 207 people using the Slovin formula, a sample of 69 people was obtained. The results of the study conclude that the hypothesis is fulfilled, namely customer interest has a positive and significant effect on the product, with an R Square of 0.748.